Penal Policy for Handling Illegal Fishing in Indonesian Exclusive Economic Zone Based on Pancasila - Marimin Marimin (Universitas Negeri Semarang, 2022)
This study discusses the policy of handling fisheries crime in Indonesia which does not run optimally between regulations and law enforcement. By using the normative juridical method by combining normative qualitative analysis and literature studies, in finding and formulating legal arguments in enforcing the law regarding the handling of fisheries crimes. The discussion of this article only focuses on regulations regarding law enforcement of fisheries crimes which have problems ranging from overlapping laws and regulations to conflicts between agencies that handle this problem, as well as criminal sanctions in the form of fines that are applied to perpetrators of illegal fishing. foreign flags are very low and there is no body confinement so that it does not cause a deterrent effect for the perpetrators. So it is necessary to make changes related to the handling of fisheries crime into a more effective form of regulation, because government policies have an important role in resolving illegal fishing legal issues in order to reduce the impact of state losses. Through policy reformulation starting from changes to laws and regulations, implementing regulations to the handling system, it can reduce the practice of illegal fishing in Indonesia.